Analisis Rencana Pelaksanaan Pembelajaran Mata Pelajaran Pendidikan Agama Islam SMP pada Materi Sejarah Islam di Andalusia melalui Pendekatan Interdisipliner - Andriawan, Irwan; Firdaus, Fadli (Perkumpulan Peneliti dan Pegiat Literasi, 2023)
Islamic Religious Education (PAI) in secondary schools plays an important role in shaping students' character and understanding of religion. Islamic history material in Andalusia is an integral part of the PAI curriculum which reflects the great civilization in the Andalusia region, Spain. This research analyzes the use of the PAI Learning Implementation Plan (RPP) on Islamic history material in Andalusia with an interdisciplinary approach based on philosophical, theological, ontological, epistemological foundations. , psychological, sociocultural, and scientific and technological developments. The research results show that the use of lesson plans that integrate this theoretical foundation increases students' understanding of the history of Islam in Andalusia, as well as increasing their motivation and interest in learning. In addition, the research identified several obstacles in the development and implementation of complex lesson plans. This research contributes to the understanding of PAI learning in secondary schools and the importance of integrating relevant theoretical foundations in increasing understanding of Islamic history and religious values.